(untitled) (Journal of Gender and Social Issues, 2018)
The purpose of the present study was to found out the effectiveness of teachers’ transactional leadership styles on students’ academic achievement. The objectives of the study were: to evaluate public and private sector college teachers’ transactional leadership style and to explore gender wise differences in public and private sector college teachers’ views about their leadership styles. The population of the study was teachers teaching secondary classes and students of 12th grade from public and private colleges registered and affiliated with Federal Board of Intermediate and Secondary Education Islamabad. Total 6 null hypotheses were developed. Data was analyzed and the major findings which were inferred from the data analysis observed no significant difference of opinion of public and private sector college teachers about transactional leadership style and no gender difference was observed about teachers’ transactional leadership style.